Immune-Related Genetic Overlap Between Regional Gray Matter Reductions and Psychiatric Symptoms in Adolescents, and Gene-Set Validation in a Translational Model - Penninck, Lukas; Ibrahim, El Chérif; Artiges, Eric; Gorgievski, Victor; Desrivières, Sylvane; Farley, Severine; Filippi, Irina; de Macedo, Carlos E. A.; Belzeaux, Raoul; Banaschewski, Tobias; Bokde, Arun L. W.; Quinlan, Erin Burke; et al. (Frontiers in Systems Neuroscience, 2021)
Here, we investigated a possible common immune-related genetic link between these two phenomena in a population study of human adolescents. Hippocampal and medial prefrontal cortex (mPFC) GM volumes were extracted from the IMAGEN database in 1563 14-year-olds recruited from the community in 4 european countries. Two polygenic risk scores (PRS) were constructed with inflammation-related SNPs; one accounting for hippocampal GM volume at age 14 and another for mPFC GM volume at age 14. We found 26 “independent” SNPs that correlated with the hippocampal volumes and 29 with the mPFC volumes. The predictive ability of both PRSs with regards to the presence of psychiatric symptoms at age 18 was investigated by correlating the PRSs with psychometric questionnaires obtained at age 18. The PRSs (but not control PRSs constructed with random SNPs) were found to have significant predictive power with regards to the presence of depressive symptoms, positive psychotic symptoms and externalizing symptoms in later adolescence. We also found that the effect of childhood maltreatment, one of the major environmental risk factors for depression and other mental disorders, interacted with the inflammation-related genetic effect. We next sought to validate this finding by investigating our set of inflammatory genes in a translational animal model of early life adversity. Mice were subjected to a protocol of maternal separation at an early post-natal age. We evaluated depressive behaviors in separated and non-separated mice at adolescence and their correlations with the concomitant expression of our genes in whole blood samples. We show that in mice, early life adversity affected the expression of our set of genes in peripheral blood, and that levels of expression correlated with symptoms of negative affects at adolescence. Overall, our translational findings in adolescent mice and men provide a novel validated gene-set of immune-related genes for further research in the early stages of mood disorders.